EVALUATION OF SCHOOL BAGS CHILDREN WITH BIOMECHANICS AND KANSEI ENGINEERING - FELICIA ALDA RIANTO NIM 13414055, LIDWINA
School bag is a crucial item for schoolchildren. Lifting and carrying school bags is daily activity for children. This can affect child growth, including their posture and risk of musculoskeletal disorders. There are two types of bags that Indonesian schoolchildren use, backpack and sling bag. This study aims to evaluate 2 types of children school bag with biomechanics approach based on EMG, posture analysis, Rate of Perceived Discomfort (RPD), Activities- Specific Balanced Confidence Scale (ABC Scale) and product evaluation based on Kansei Engineering . The study was conducted through an experiment involving 12 child respondents. Each respondent was asked to perform simulations of carrying schoolbag with 2 different types and 2 different weights (2,4 kg and 15% body weight). There are 4 muscles that will be the focus of this study there are upper trapezius muscle (right-left) and erector spinae muscle (right-left) and 4 angles for postural assesment there are craniohorizontal angle, craniovertebral angle, sagittal shoulder angle, and acromioclavicular joint deviation angle. Product evaluation was done by identifying the kansei words to 15 respondents and distributing the level of importance questionnaire to 100 respondents. The results of the study with biomechanical approach show that contraction of shoulder and back muscle is higher when lifting sling bag. The difference in acromiovicular joint angle is greater between the conditions when the sling bag is used. Level of confidence in balance felt by respondents is lower when lifting sling bag at 15% body weight. . Whereas the measurement with RPD shows the comfort level felt by respondents for sling bag on weight of 2,4 kg more uncomfortable than backpack. The results of product evaluation includes attributes of products that have been in accordance with consumer emotions, as well as and guideline for schoolbagÃ‚Â’s usage Keywords: school bags, children, musculoskeletal